1996
DOI: 10.1002/marc.1996.030170706
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and dynamic mechanical relaxation of poly(ether ether ketone)/poly(etherimide) blends below the glass transition

Abstract: Dielectric relaxation spectroscopy (DRS) and dynamic mechanical thermal analysis (DMTA) were used to investigate the secondary relaxation behaviour of poly(ether ether kctone) (PEEK), poly(etherimide) (PEI) and a miscible PEEKPEI blend. The data from each technique, for the y-process, did not lie on the same Arrhenius line, ivhile the rate of molecular motion of the y-process in the blends was largely an average of each component's motions. The B-process in PEI was plasticised by the presence of PEEK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…10 show that the activation energy remains in the same range of magnitude (* 45 kJ mol -1 ) for all the thermal treatments for both polymers. Our values remain consistent with the literature for PEEK [23,54]. As there is a very similar behaviour between PEEK and PAEK LM (by DMA and DDS), the localized mobility of both polymers and their molecular origin are probably the same: oscillations of aromatic rings near polar regions interacting with water molecules.…”
Section: B Relaxationssupporting
confidence: 91%
See 1 more Smart Citation
“…10 show that the activation energy remains in the same range of magnitude (* 45 kJ mol -1 ) for all the thermal treatments for both polymers. Our values remain consistent with the literature for PEEK [23,54]. As there is a very similar behaviour between PEEK and PAEK LM (by DMA and DDS), the localized mobility of both polymers and their molecular origin are probably the same: oscillations of aromatic rings near polar regions interacting with water molecules.…”
Section: B Relaxationssupporting
confidence: 91%
“…Both PEEK and PAEK LM displayed the b 2 mechanical relaxation at the same temperature (-58°C) that strengthen the similarity of the two polymers. The literature identifies the b 2 relaxation as the localized mobility of aromatic rings in various PAEK polymers [21,22,54]. Quiroga et al [21] have also observed the b 2 relaxation of PEKK which is located at higher temperature than the PEEK one, probably due to a lower proportion of Ether moieties.…”
Section: B Relaxationsmentioning
confidence: 99%
“…The fast secondary or γ-relaxation was detected in PEI and characterized by different techniques, namely by Dynamic Mechanical Thermal Analysis (DMTA), 6,18 Dielectric Relaxation Spectroscopy (DRS) 6,18,19 and TSDC. 6 It appeared in the deep amorphous solid state, more than 100 degrees below the glass transition temperature, T g .…”
Section: The Different Types Of Mobilitymentioning
confidence: 99%
“…Recently, we have explored the miscibility of PEEK/PEI blend at the molecular level through free volume studies using PALS . On the other hand, DMTA studies were focused mainly on miscibility and relaxation process in PEEK, PEI, and their blends . In spite of the prominent utility of PEEK and its blends in aerospace applications, there are no scientific reports to understand the damping behavior of this blend to the available free volume in it.…”
Section: Introductionmentioning
confidence: 99%
“…3 On the other hand, DMTA studies were focused mainly on miscibility and relaxation process in PEEK, PEI, and their blends. 6,[42][43][44] In spite of the prominent utility of PEEK and its blends in aerospace applications, 8 there are no scientific reports to understand the damping behavior of this blend to the available free volume in it. In this work, we have made an attempt to explore the free volume and damping properties in this blend using PALS and DMTA techniques.…”
Section: Introductionmentioning
confidence: 99%